The Effectiveness of Mobile Learning in Remote and Rural Areas - Wahyuni, Erna; Khan, Omar; Raza, Amir (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Access to quality education in remote and rural areas remains a global challenge due to geographical isolation, lack of infrastructure, and limited resources. Mobile learning (m-learning) has emerged as a potential solution to bridge this gap, offering flexible and accessible education through mobile devices. This study aims to evaluate the effectiveness of mobile learning in remote and rural areas, focusing on its impact on student engagement, learning outcomes, and the challenges associated with its implementation. A mixed-methods research design was employed, combining quantitative surveys and qualitative interviews with students and teachers from rural schools that have adopted mobile learning platforms. The study involved 250 students and 50 teachers across three regions. Quantitative data was analyzed to assess learning outcomes, while qualitative data provided insights into the user experience and challenges faced in implementing m-learning. The findings reveal that mobile learning significantly improves student engagement, with 70% of students reporting increased motivation to learn due to the flexibility and accessibility of m-learning. However, technical challenges such as poor internet connectivity and limited access to devices were noted as barriers to full adoption. Despite these challenges, 65% of teachers reported positive changes in student performance and participation. In conclusion, mobile learning offers a promising solution for enhancing education in remote and rural areas. While it significantly improves engagement and learning outcomes, addressing the technical and infrastructural barriers is crucial for maximizing its potential. The study suggests that with proper investment in infrastructure, m-learning can be an effective tool for bridging educational disparities in underserved regions.